When Do Multinational Companies Consider Corporate Social Responsibility? A Multi‐country Study in Sub‐Saharan Africa. (June 2017) - Görg, Holger; Hanley, Aoife; Hoffmann, Stefan; Seric, Adnan
Abstract: While African countries are becoming more and more relevant as host countries for suppliers of multinational companies little is known about corporate social responsibility (CSR) in this region. To fill this gap, the present article explores CSR considerations of foreign affiliates of multinational companies when choosing local African suppliers. The article suggests a model of three types of determinants, namely firm characteristics, exports, and intra‐trade. Analyses of a large‐scale and quite unique firm level data for more than 2, 000 foreign owned firms in 19 sub‐Saharan African countries demonstrate that firms importing intermediates from their parent company abroad are more likely to implement CSR. Similarly, CSR plays a larger role for affiliates that export to developed countries. Different determinants affect environmental and social CSR activities.